Chocolate cities: A brief note from a race and capitalism perspective. Issue 3 (17th February 2019) - Dawson, Michael
ABSTRACT: Marcus Hunter and Zandria Robinson have provided us with an innovative methodology for analysing "maps" of African Americans' lived political, social and cultural experiences past and present. Their powerful innovation is creating maps of the black experience based on black people's lived experience. They argue that carefully tracing spatially blacks' political, social and cultural patterns over time leads one to the conclusion that the shared experiences of blacks throughout the polity (and indeed throughout the Diaspora) have far more in common than not. I argue that we can better understand not only the maps that black people have created, but also chocolate cities themselves by using an analytical framework that integrates the analysis of the lived experience of black people with a structural analysis that interrogates the articulation of white supremacy, capitalism and patriarchy. This framework is related to the developing research into racial capitalism that is now being conducted globally.